1996
DOI: 10.1007/bf01887400
|View full text |Cite
|
Sign up to set email alerts
|

The nanometer-scale structure of amyloid-Β visualized by atomic force microscopy

Abstract: Amyloid-beta (A beta) is the major protein component of neuritic plaques found in Alzheimer's disease. Evidence suggests that the physical aggregation state of A beta directly influences neurotoxicity and specific cellular biochemical events. Atomic force microscopy (AFM) is used to investigate the three-dimensional structure of aggregated A beta and characterize aggregate/fibril size, structure, and distribution. Aggregates are characterized by fibril length and packing densities. The packing densities corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
126
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(137 citation statements)
references
References 43 publications
(39 reference statements)
11
126
0
Order By: Relevance
“…18 of these derivatives were based on the A␤40 peptide, and one derivative, 42R1, was based on the longer A␤42 peptide. All fibrils grown from the R1-labeled A␤ peptides display morphologies similar to those previously reported for wild type A␤ (27)(28)(29)(30). According to atomic force microscopy, electron microscopy of negatively stained samples, and thioflavin T fluorescence measurements, the introduction of R1 at each of the 19 positions did not significantly affect the ability of these modified peptides to form fibrils (data not shown).…”
Section: Fibril Formation Of R1-labeled A␤ Results In Significantsupporting
confidence: 81%
See 1 more Smart Citation
“…18 of these derivatives were based on the A␤40 peptide, and one derivative, 42R1, was based on the longer A␤42 peptide. All fibrils grown from the R1-labeled A␤ peptides display morphologies similar to those previously reported for wild type A␤ (27)(28)(29)(30). According to atomic force microscopy, electron microscopy of negatively stained samples, and thioflavin T fluorescence measurements, the introduction of R1 at each of the 19 positions did not significantly affect the ability of these modified peptides to form fibrils (data not shown).…”
Section: Fibril Formation Of R1-labeled A␤ Results In Significantsupporting
confidence: 81%
“…It has previously been reported that A␤ fibrils are polymorphic and display different diameters and morphologies, including smooth, twisted, and branched fibers and fiber bundles (27)(28)(29)(30). These polymorphisms are dependent upon the time of incubation and conditions used.…”
Section: Comparison Of Motion In A␤ Fibrils and Globular Proteins-mentioning
confidence: 99%
“…In the presence of monomeric Aβ, all these species convert to mature amyloid fibrils by monomer addition. Mature amyloid fibrils have been described as insoluble, β-sheet-rich structures that are more than 1 µm long, 8-12 nm in diameter and composed of 2-6 protofilament subunits 24,25 . In vitro, synthetic and recombinant forms of Aβ peptides have been shown to form aggregates and amyloid fibrils that are indistinguishable from the ones isolated from AD brain [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…However, several laboratories including our own have provided evidence supporting the existence of numerous preamyloid quaternary structural intermediates (7,16,17). These intermediates seem to play a major role in the amyloid fibril formation process and possibly in the pathological mechanism of amyloid disease (2,17,18).…”
mentioning
confidence: 96%